Factors influencing the variation of microplastic uptake in demersal fishes from the upper Thames River Ontario. (15th November 2022) - Wardlaw, Colleen M.; Corcoran, Patricia L.; Neff, Bryan D.
Abstract: Microplastics (plastic particles <5 mm) are abundant in aquatic environments, particularly near urban areas. Little is known, however, about how variations in microplastic abundances within watersheds affect fishes. Microplastics were examined in demersal fishes—white sucker ( Catostomus commersonii ) and common carp ( Cyprinus carpio )—across 11 sites in the Thames River, Ontario, Canada. Microplastics were found in 44% of white sucker, ranging from 0 to 14 particles per fish, and 31% of common carp, ranging from 0 to 128 particles per fish. Across both species, the number of microplastics was higher in urban sites than rural sites, and there was a positive relationship between the number of microplastics in the fish and the abundance of microplastics in the sediment. Body mass was also positively related to number of microplastics in fish. Together these results provide insight into environmental and biological factors that may be influencing microplastic ingestion in demersal fishes. Graphical abstract: Image 1 Highlights: Demersal river fish ingested fragments, fibres and tire wear particles. 44% of white sucker and 31% of common carp contained at least one particle. Microplastic in fish were related to body mass and land use; not species dependent. Amount of microplastics in sediment may be useful to indicate amounts in fish.